Convexity and sheepskin effects in the human capital earnings function : recent evidence for Filipino men - Schady, Norbert Rüdiger, 1967- 1967- (Policy research working paper, 2001)
Data on education in the Philippines show that there are large differences in the private rate of return to education by level: the wage premia associated with an additional year of schooling are about twice as large at the university level as they are at the primary school level. In addition, there are large "sheepskin effects." Completion of the last year of schooling within a given level is rewarded disproportionately, particularly for university graduates